Quality of Life and Mood of Patients and Family Caregivers during Hospitalization for Hematopoietic Stem Cell Transplantation - El-Jawahri, Areej (Cancer, 2014)
BACKGROUND: To investigate the impact of hospitalization for hematopoietic stem cell transplantation (HCT) on patients’ and family caregivers’ (FC) quality of life (QOL) and mood. METHODS: We conducted a longitudinal study of patients hospitalized for HCT and their FC. At baseline (6 days pre-HCT), day+1, and day+8 of HCT, we assessed QOL (Functional Assessment of Cancer Therapy-Bone Marrow Transplantation FACT-BMT), and mood (Hospital Anxiety and Depression Scale HADS). We administered the SF-36 to examine FC QOL [physical component scale (PCS), and mental component scale (MCS)]. To identify predictors of QOL changes, we used multivariable linear mixed models. RESULTS: We enrolled 97% of eligible patients undergoing autologous (n=30), myeloablative (n=30) or reduced intensity (n=30) allogeneic HCT. Patients’ QOL markedly declined (mean FACT-BMT 109.6 to 96.0, P < 0.0001) throughout hospitalization. The proportion of patients with depression (HADS-Depression> 7) more than doubled from baseline to day+8 (15.6% to 37.8%, P < 0.0001), whereas the proportion of patients with anxiety remained stable (22.2%, P = 0.8). These results remained consistent when data were stratified by HCT type. Baseline depression (β= −2.24, F=42.2, p < 0.0001) and anxiety (β= −0.63, F=4.4, p = 0.03) independently predicted worse QOL throughout hospitalization. FC QOL declined during patient’s hospitalization (PCS: 83.1 to 79.6, P= 0.03, MCS: 71.6 to 67.4, P = 0.04). CONCLUSIONS: Patients undergoing HCT reported a steep deterioration in QOL and substantially worsening depression during hospitalization. Baseline anxiety and depression predicted worse QOL during hospitalization, underscoring the importance of assessing pre-HCT psychiatric morbidity.